Effect of Vitamin D Deficiency on Gestational Diabetes Mellitus: A Meta-Analysis - Dian Handayani; Eti Poncorini Pamungkasari; Bhisma Murti (Journal of Epidemiology and Public Health, 2023)
Background: Gestational diabetes mellitus increases the risk of a number of short-term and long-term health problems in both mother and baby. Some evidence states that one of the causes of gestational diabetes mellitus is vitamin D deficiency. This study aimed to estimate the magnitude of the influence of vitamin D deficiency on the incidence of gestational diabetes mellitus, through a meta-analysis of previous primary studies. Subjects and Method: This was a systematic review and meta-analysis with the following PICO, population: pregnant women, intervention: vitamin D deficiency, comparison: no vitamin D deficiency, outcome: gestational diabetes mellitus. The articles used in this study were obtained from four databases, namely PubMed, Google Scholar, Science Direct, and Springer Link, using the search keys "Vitamin D Deficiency"[Mesh] OR “Vitamin D Deficiency”[tw] AND "Diabetes, Gestational" [Mesh] OR “Gestational Diabetes Mellitus”[tw] OR “Gestational Diabetes”[tw]. The included article is a full-text cohort study design from 2018 to 2022 and reports the adjusted odds ratio (aOR) in a multivariate analysis. The selection of articles is done using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application. Results: A total of 9 cohort studies involving 42,972 pregnant women from the continents of Asia, Australia and Europe were used in the meta-analysis. Pregnant women with vitamin D deficiency had a risk of gestational diabetes mellitus 1.87 times compared to those without vitamin D deficiency (aOR= 1.87; 95% CI= 1.27 to 2.75; p= 0.002). Conclusion: Vitamin D deficiency increases the risk of developing gestational diabetes mellitus. Keywords: vitamin D deficiency, gestational diabetes mellitus, pregnancy Correspondence:Dian Handayani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A Surakarta 57126, Central Java, Indonesia. Email: dianhan1812@gmail.com. Mobile: +6285876686231.